Drug-Induced Sleep Endoscopy as an Effective Diagnostic Tool for Obstructive Sleep Apnea - Zin, Dmytro; Shydlovska, Tetiana (The Ukrainian Scientific Medical Youth Journal, 2025)
sleep-disordered breathing, particularly obstructive sleep apnea, is a prevalent condition characterized by partial or complete upper airway collapse during sleep. It may lead to hypoxemia, sleep fragmentation, and the development of comorbid conditions. An effective method for identifying the site and nature of obstruction is drug-induced sleep endoscopy, which can be performed either during natural sleep or under pharmacological sedation. The aim of this study was to assess the diagnostic value of drug-induced sleep endoscopy using dexmedetomidine. The study included 36 patients aged 22 to 47 years, divided into three groups: natural sleep (n=12), sedation with propofol (n=12), and sedation with dexmedetomidine (n=12). The shortest procedure duration was recorded in the dexmedetomidine group (17.83±3.00 min), compared to the natural sleep group (31.17±2.02 min). The frequency of complications, such as apnea or bradycardia, did not differ significantly between groups. These findings suggest that drug-induced sleep endoscopy using dexmedetomidine is an effective and safe alternative that reduces examination time without increasing the risk of adverse events.